Measures Adopted in Nepalese Organization to Motivate Employees - Aryal, Narayan Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
There is a growing concern for motivation these days because every organization feels needs to use its human resource at optimum level. There have always been issues to identify what factors motivate the employee? Is it financial or non-financial? What should be the proportion of financial and non-financial? What do people prefer in the organization while they work? These have been the major issues this article discusses and tries to answer. The sources of data are primary and secondary. The literature is critically analyzed.